PETROLOGY OF A MEGACRYST ASSEMBLAGE IN PLIOCENE-PLEISTOCENE BASANITES FROM THE VITIM PLATEAU (TRANSBAIKALIE) - Litasov K.D. (My University, 2000)
The megacryst assemblage of Pliocene-Quaternary basanites from the Vitim Plateau comprises clinopyroxene, garnet, ilmenite, Ti-magnetite, biotite, and K-Na-feldspar megacrysts. This assemblage also includes large aggregates of clinopyroxene with garnet, ilmenite, and phlogopite, and also ilmenite-clinopyroxene symplectites. The chemical variation trend of the clinopyroxene megacrysts shows increasing TiO2, Al2O3, Na2O, and CaO concentrations, a decreasing Cr2O3 content, and a declining Mg-number. This trend agrees with a model of polybaric magma fractionation in magma-produced fractures and local magma chambers. As magma rose toward the Earth's surface, it experienced differentiation: crystals of particular minerals precipitated on the walls of fractures and magma chambers. The crystallization temperature of the clinopyroxene megacrysts decreased from 1350 to 1000°C as their Mg-number declined. Empirical pressure estimates are 25-14 kbar. Apparently each volcano had its own dike system extending to depths of 60-80 km, the magma composition in the source being almost invariable: the data points of the megacrysts fall on different segments of the same trend. The following sequence of mineral deposition was established: clinopyroxene, clinopyroxene±garnet, clinopyroxene, clinopyroxene+garnet, clinopyroxene+ilmenite+biotite, and K-Na-feldspar.
Keywords: Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен